Phenotype variability and basic morphological characteristics of the Aksaray Malakli dog population in Turkey - Urošević, Milivoje, veterinar; Matejević, Milosava; Drobnjak, Darko; Ozkanal, Umit (2021)
The Turkish Mastiff or Aksaray Malakli Dog is a Turkish dog breed not yet officially recognized by the world canine organization - Fédération Cynologique Internationale (FCI). To achieve recognition, more research and analysis of the morphometric parameters of this breed are required. Previous research on this breed presented the average values of certain morphological parameters. Measurement results of 20 morphometric parameters showed that there are statistically significant differences in body structure between males and females. Such results are significant for setting the official breed standard in which the proportions of the body characteristic of this breed should be emphasized.
Turski mastif ili aksaray malakli je turska pasmina pasa koju Svjetska kinološka organizacija - Fédération Cynologique Internationale (FCI) još nije službeno priznala. Kako bi ova pasmina bila priznata, potrebna su brojna istraživanja i analiza morfometrijskih parametara ove pasmine. Prethodno istraživanje na ovoj aksaray malakli pasmini pokazalo je prosječne vrijednosti nekih morfoloških parametara. Mjerenje rezultata 20 morfometrijskih parametara pokazalo je da postoje statistički značajne razlike u tjelesnoj strukturi između mužjaka i ženki. Takvi rezultati su značajni za postavljanje službenog standarda pasmine u kojem bi trebalo naglasiti proporcije tjelesnih karakteristika ove pasmine.
Bibliografija: 6 jed.
Abstract ; Sažetak.
Keywords: Psi -- Pasmine -- Turski mastif -- Morfometrija